(untitled) (The Research of Medical Science Review, 2025)
Cerebral palsy (CP) is among the most common causes of childhood disability, with motor dysfunction and impaired balance representing major challenges especially in the hypotonic subtype. This randomized controlled trial examined the effects of adding vestibular stimulation to routine physiotherapy on motor skills and postural stability in children with hypotonic CP. Eighty‐two children meeting strict inclusion criteria were randomly allocated to either a combined treatment group (vestibular stimulation plus conventional therapy) or a conventional therapy only group. Outcome measures included the Gross Motor Function Measure (GMFM), Pediatric Balance Scale (PBS), and Pediatric Evaluation of Disability Inventory (PEDI), administered at baseline and following a six‐week intervention period. Data analysis revealed that children receiving vestibular stimulation demonstrated statistically significant improvements in both gross motor function and balance compared to their counterparts receiving conventional therapy alone. These findings support the clinical integration of vestibular stimulation as an adjunct to standard rehabilitation in this population.